A meta‐analysis of ethnic differences in pathways to care at the first episode of psychosis. (28th February 2014) - Anderson, K. K.; Flora, N.; Archie, S.; Morgan, C.; McKenzie, K.
<x xml:space="preserve">Abstract</x> Objective We sought to systematically review the literature on ethnic differences in the likelihood of general practitioner (GP) involvement, police involvement, and involuntary admission on the pathway to care of patients with first‐episode psychosis (FEP). Method We searched electronic databases and conducted forward and backward tracking to identify relevant studies. We calculated pooled odds ratios (OR) to examine the variation between aggregated ethnic groups in the indicators of the pathway to care. Results We identified seven studies from Canada and England that looked at ethnic differences in GP involvement (n = 7), police involvement (n = 7), or involuntary admission (n = 5). Aggregated ethnic groups were most often compared. The pooled ORs suggest that Black patients have a decreased likelihood of GP involvement (OR = 0.70, 0.57–0.86) and an increased likelihood of police involvement (OR = 2.11, 1.67–2.66), relative to White patients. The pooled ORs were not statistically significant for patients with Asian backgrounds (GP involvement OR = 1.23, 0.87–1.75; police involvement OR = 0.86, 0.57–1.30). There is also evidence to suggest that there may be ethnic differences in the likelihood of involuntary admission; however, effect modification by several sociodemographic factors precluded a pooling of these data. Conclusion Ethnic differences in pathways to care are present at the first episode of psychosis.